Dominant Factors Cause Students with Special Needs (Deaf) in Solving Mathematics Problems - Musli, Ana Muliana; Fitriani, Fitriani; Aprisal, Aprisal (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This research objective is to describe the dominant factors that cause students with special needs (deaf) to solve mathematics problems. This research is qualitative descriptive research with a case study approach. The research was carried out at SLB Negeri Lutang Kab. Majene. The subjects of this research were seven people, consisting of three deaf students, three parents, and one teacher. The instruments used in this research consisted of observation sheets and interview guidelines. The data analysis techniques used consist of data reduction, data presentation, and conclusion. Based on the results of the data analysis, it was concluded that the factors that influence deaf students to solve mathematics problems consist of two factors, namely internal factors, and external factors. Internal factors consist of learning interest, learning habits, and student learning motivation. Meanwhile, external factors consist of the influence of the family environment and the school environment.